THE SPEECH ACT ANALYSIS OF DIRECT UTTERANCES ON SHORT STORY "THE LOST BEAUTIFULNESS” BY ANZIA YEZIERSKA - Satiul Komariah (EduLite: Journal of English Education, Literature and Culture, 2017)
This research aimed to investigate (1) the form of direct sentences on short story entitled The Lost “Beautifulness”, (2) analyze the purpose of the direct utterances in the short story, (3) show the kind of direct utterances in short story The Lost “Beautifulness”. The object used in this research are direct utterances of short story The Lost “Beautifulness”. The data were collected by observation method. The writer selecting the direct utterances which can be found in the short story. The result of the research showed that: (1) three forms of the direct utterances are declarative, interrogative and imperative sentence; (2) purposes of the utterances depend on the four factors; locution, illocution, perlocution and social context; (3) seven kinds of speech acts are assertive, performative, verdictive, expressive, directive, commisive and phatic utterances.Keywords: Speech act, Direct Utterance, Short Story